Can lower extremity anatomical measures and core stability predict dynamic knee valgus in young men?. (July 2021) - Mozafaripour, Esmaeil; Seidi, Foad; Minoonejad, Hooman; Mousavi, Seyed Hamed; Bayattork, Mohammad
Abstract: Introduction: Dynamic knee valgus (DKV) is a risk factor for lower extremity injuries such as anterior cruciate ligament and patellofemoral pain syndrome. Purpose of the current study was to investigate the relationship between lower extremity anatomical measures (LEAM) and core stability with DKV during the single-leg squat. Methods: Thirty healthy men aged between 18 and 28 years participated in this cross-sectional biomechanical study.DKV was assessed using a 6-camera motion analysis system during a single-leg squat task. Anteversion of hip, hip internal and external rotation, Q-angle, knee hyperextension, tibial torsion, tibia vara, plantar arch index, and core stability were measured using standard clinical procedures. To predict DKV, a multiple linear regression model was used. Result: The stability index negatively and plantar arch index positively predicted greater DKV during the single-leg squat task (P = 0.001 and P = 0.09, respectively). Research variables together predicted 82% of the variance in DKV (F(4, 26) = 28.09, p < 0.001). However, relationships between other variables and DKV were not found. Conclusion: The core stability index and plantar arch index were associated with observed DKV during the single-leg squat. These results suggested that proximal and distal variables to the knee should be considered when evaluating individuals who present DKV during the single-leg squat. Highlights: The core stability index and plantar arch index were associated with Dynamic knee valgus. Proximal and distal variables to the knee should be considered when evaluating individuals with Dynamic knee valgus. Clinicians should consider core stability and plantar arch indexes when designing intervention programs for knee valgus.